PENGARUH KONSENTRASI SUBSTRAT PADA PEMBUATAN MALTODEKSTRIN DARI SUBSTRAT PATI SAGU: (Effect Of Substrate Concentration Variation In Maltodextrin Production From Sago Starch) - Amran Laga; Andi Dirpan; Aisyah Amini Anshari (Hasanuddin University Food Science and Technology Study Program, 2018)
The aims of this research were to examine the effect of the optimal sago substrate concentration to produce maltodextrin. This research consists of two factors. First factor was sago concentration that consists of 4 levels (20%, 25%, 30% and 35%) and the second was time of liquefaction that consisting of 7 levels (0 minutes, 20 minutes, 40 minutes, 60 minutes, 80 minutes, 100 minutes, and 120 minutes). Parameters of observation were reducing sugar levels, total solid, the values equivalent dextrose, residual starch and viscosity. Data were analyzed using a completely randomized design if treatment had real effect on parameter then continued with Duncan test. The result of the research was the best concentration in maltodextrin hydrolysis was in concentration of 35% in terms of reducing sugar levels, total solids, equivalent dextrose and viscosity with each value 138.69 g / L, 39.41%, 35.37% and 5021.43 cP. While the he best reaction time liquefaction of maltodextrin at 120 minutes with reducing sugar levels, total solid, the values dextrose equivalent and viscosity with each value of 158.25 g / L, 41.28%, 38.35% and 1701.42 Cp